IMPLIKATUR PERCAKAPAN TOKOH WANITA DAN TOKOH LAKI-LAKI DALAM FILM HARRY POTTER AND THE GOBLET OF FIRE - Yunita Nugraheni (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2011)
As a human, people always do communication with others. Communication has several functions, such as, conveying idea and giving information to others. One main requirements needed by person who doing communication is make sure that the listener or people involved in the conversation will cooperate each other. So, the communication can run well. Paul Grice on 1975 stated the Cooperative Principle. The Cooperative Principle of conversation is elaborated in four sub-principles called maxims. They are maxim of quantity, maxim of quality, maxim of relevance and maxim of manner. Furthermore, this research also tries to discover the differences of women and men in applying the Cooperative Principle.